The key long non‐coding RNA screening and validation between germinal vesicle and metaphase II of porcine oocyte in vitro maturation. Issue 3 (23rd January 2020) - Jiao, Yafei; Gao, Bangjun; Wang, Guodong; Li, Hui; Ahmed, Jam Z.; Zhang, Dandan; Ye, Sheng; Liu, Shulin; Li, Mengmei; Shi, Deshun; Huang, Ben
Abstract: Oocyte maturation plays a vitally important role in the reproduction of pigs. However, the roles of messenger RNAs (mRNAs) and long non‐coding RNAs (lncRNAs) in the developmental process of porcine oocyte maturation are still largely unclear. In this study, a transcriptome analysis of germinal vesicle (GV) and metaphase II (MII) of oocytes from Chinese Duroc pigs was performed. A total of 1, 753, 030 and 2, 486 differentially expressed (DE) mRNAs, 22, 811 and 9, 868 DE lncRNAs were identified between GV and MII stages, respectively. Furthermore, functional enrichment analysis showed that the common DE mRNAs and DE lncRNAs during the process of maturation were mainly involved in biological process and cellular components. Our study provides new insights of the expression changes of mRNAs and lncRNAs during GV and MII stages, which might contribute to the maturation of oocytes. These results greatly improve our understanding of the molecular mechanisms regulating the maturation of oocytes in pigs.